Providing an Effective Model of Good Governance Based on the Criteria Proposed by Muslim Thinkers for Organizational Health in Governmental Organizations in Kerman Province - Safary zadeh Bezenjani, Taherh (2020)
Good governance is an unavoidable requirement to improve the health of the administrative system in a society. Thus, the purpose of this study is to design an effective model of good governance based on the proposed criteria of Muslim thinkers for organizational health in governmental organizations in Kerman province. Regarding the purpose, this research is applied, it is descriptive of correlational type in terms of nature, and is survey considering method. The statistical population includes all employees and managers working in governmental organizations and offices in Kerman (2310 people). The sample size was estimated to be 321 based on Morgan's table, and were chosen by simple random sampling. A researcher-made questionnaire was used to gather data. The validity of the good governance questionnaire was 94% based on the proposed criteria of Muslim thinkers and the validity of the organization's health questionnaire was 93%. The reliability coefficient of the questionnaires was calculated to be 0.91 and 0.88; respectively. Spearman correlation test through SPSS software was used to analyze the data. Based on the results at a significant level of less than 0.05, the correlation coefficients of Spearman between the components of: accountability and the right to express good governance (0.156), political stability and the absence of good governance violence (0.154), the effectiveness of government Good governance (0.122), regulatory quality of good governance (0.238), the authority of good governance law (0.342), and the inhibition of good governance corruption (0.178) and organizational health were positive and significant. Considering that the capacity of a governing system to support the country's macro-strategies and policies for public welfare is increasingly recognized as the basis for the progress and development of society, government officials should double their efforts to solve the problems in the field of health system for achieving the goals of the upstream documents.